The Spectrum of C4d Deposition in Renal Biopsies of Lupus Nephritis Patients - Ding, Ying; Yu, Xiaojuan; Wu, Lihua; Tan, Ying; Qu, Zhen; Yu, Feng (Frontiers in Immunology, 2021)
Objectives: This study aims to determine the prevalence and localization of complement factor C4d in renal biopsies of lupus nephritis (LN) patients, as well as its association with the clinico-pathological features of the disease. Especially, the correlation between arteriolar C4d deposition and renal microvascular lesions (RVL) was further analyzed. Methods: A total of 325 biopsy-proven lupus nephritis patients were enrolled and their clinico-pathological data were collected. C4d staining in renal biopsies was performed by immunohistochemistry. The association between C4d deposition and the clinico-pathological features was further analyzed. Results: C4d deposition was present in most of renal specimens (98.8%) in our cohort. They were localized in the glomeruli (98.2%), tubular basement membrane (TBM) (43.7%), arterioles (31.4%) and peritubular capillary (33.8%), respectively. TBM C4d staining was closely related to the disease activity (SLEDAI) and NIH pathological activity and chronicity indices (P<0.01). Patients with arteriolar C4d deposition were more likely to develop RVL (91.2%) in comparison to those negative (78.0%; P=0.004), especially with two or more types of RVL (P<0.001). During an average follow-up of 55.8 months, the presence of arteriolar C4d was related to worse renal outcomes (HR: 2.074, 95% CI 1.056-4.075, P=0.034). Co-deposition of arteriolar C4d and C3c was an independent risk factor (HR: 2.539, 95% CI 1.130-5.705, P=0.024) for predicting renal outcomes by the multivariate stepwise Cox hazard analysis. Conclusions: C4d deposition was common in renal tissues of lupus nephritis patients. TBM C4d deposition was related to the disease activity and arteriolar C4d deposition was associated with RVL and worse renal outcomes.